Parents’ knowledge and attitudes of children treated at the University Children’s Hospital in Lublin towards influenza vaccinationw - Jankowska, Paula Katarzyna; Jankowski, Krzysztof Jacek; Nowakowska, Luiza (Journal of Education, Health and Sport, 2018)
Introduction: In recent times, there is an intense debate on the the merits of the use of vaccination and post-vaccination complications among Poles. Vaccination against influenza is recommended in Poland. Many of the opponents use arguments which are not scientifically substantiated but widely widespread. Statistics show that the percentage of Poles who decide on vaccination, continues to decline. Aim: The aim of this work is to evaluate level of knowledge about influenza vaccinations among parents of children treated in University Children’s Hospital of Lublin. Material and methods: There were 90 participants who filled surveys prepared by the authors of the study. Data analysis was performed using STATISTICA 12.5. Results: The observed percentage of parents who do vaccinate their children was low - only 17.8% The main reasons for the resignation are: fear of adverse side effects (53.3%) and financial reasons (15.6%). Nearly half of parents believe that a healthy diet and daily doses of vitamin C to prevent flu and points to the effectiveness of antibiotics in the treatment of influenza. 14.4% believe that the influenza is the same as cold Over 30% say that regular vaccination weakens our immune system. Most frequently chosen sources of knowledge, from which parents derive knowledge about influenza vaccination, are: Internet (64.4%), doctor (42.2%) and TV (32.2%). Conclusions: Most participants in the study presents a relatively low level of knowledge about influenza vaccination, and most of them are aware of the seriousness of this disease. Lack of knowledge about the basic facts about vaccination, may be the cause of the low percentage of vaccinated children. A large part of the parents renounces vaccination due to financial problems.